2009
DOI: 10.1007/s10570-009-9359-0
|View full text |Cite
|
Sign up to set email alerts
|

Composition of lignocellulosic surfaces: comments on the interpretation of XPS spectra

Abstract: The surface compositions of lignocellulosic materials are critical to their end use performance. X-ray photoelectron spectroscopy (XPS) measures the elemental composition sampling of a very thin surface layer, and has long been used to assess the surface composition of dry lignocellulosic materials. The method is based on the quantification of carbon and oxygen XPS peak sizes and shapes, but care is necessary to minimize the effects of surface contamination and degradation. We review the XPS method, and presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…To further understand this effect, the surface lignin content of the lignocellulosic biomass was evaluated using a method adapted by Gray et al (2010) and Chen et al (2015a). X-ray photoelectron spectroscopy (XPS) measurement of carbon and oxygen signals of handsheets made from the unrefined and refined biomass (Table 2) indicated that there was a slight decrease in the calculated surface lignin in the 150 °C refined biomass compared with the ambient temperature refining and the unrefined control.…”
Section: Effect Of Refining Temperature On the Efficiency Of Enzymatimentioning
confidence: 99%
“…To further understand this effect, the surface lignin content of the lignocellulosic biomass was evaluated using a method adapted by Gray et al (2010) and Chen et al (2015a). X-ray photoelectron spectroscopy (XPS) measurement of carbon and oxygen signals of handsheets made from the unrefined and refined biomass (Table 2) indicated that there was a slight decrease in the calculated surface lignin in the 150 °C refined biomass compared with the ambient temperature refining and the unrefined control.…”
Section: Effect Of Refining Temperature On the Efficiency Of Enzymatimentioning
confidence: 99%
“…10), the C signal can be resolved into several component peaks, which reflect local environments of different C atoms (such as C C, C H, C O or O C O) (Doris and Gray, 1979;Gray et al, 2010). For our samples, the three component peaks were categorized by the bonding type of various C atoms of the CNs.…”
Section: Xps Characterizationmentioning
confidence: 99%
“…Theoretically, the XPS spectrum of cellulose exhibits C1s peaks only at a binding energy of 286.6 eV (C-O, alcohol or ether) and 288.1 eV (O-C-O, diether or carbonyl) with a relative intensity ratio of 5:1, and the C1s expressed at 285.0 eV (C-C/C-H, aliphatic) binding energy are not characteristic of cellulose; rather, they may be derived from lignin, fatty acids, or waxes. (Sapieha et al 1990;Belgacem et al 1995;Mitchell et al 2005;Gray et al 2010). According to Table 3, the value of O/C ratio was lower than the theoretical value of pure cellulose 0.83 (Gray et al 2010).…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%